The Ethics of Modernism : Moral Ideas in Yeats, Eliot, Joyce, Woolf, and Beckett - Oser, Lee (Cambridge University Press, 2013)
Human nature restores a perspective on modernism that has been lost. Without this perspective, we can see little of the modernist moral project, which is to transform human nature through the use of art. Why should we remember the block of marble, dragged through the squalid province, before the breath of genius gave it life? Or more accurately, why remember the dray and the windgalled animal that pulled it, when we bask in the favor of Toyota and Boeing, NASA and Maersk? And yet the old question has unmistakably returned: what good is there in human nature?